(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article focuses on of the study of active processes in the development of Ukrainian vocabulary the 1980-s to the present on the material of the new Explanatory Dictionary of Ukrainian Language in 20 volumes. Semantic neologisms are studied with component analysis. Basic semantic process including metaphorization, that has caused appearance of new meanings, are characterized.